The Impact of Mouth Masks on Oral Hygiene Status, Seeking Dental Care, Esthetics, and Temporomandibular Joint Disturbances Among the Adult Population in Nellore District: A Cross-sectional Study - Gayathri Priya Varshini; Kiranmayi Govula; Lavanya Anumula; Yendluri Pavan Kumar; M. Kowmudi; Soudagiri Chandrasekhar (Wolters Kluwer Medknow Publications, 2024)
Background Despite preventing infection transmission, because of its prolonged use, the impact of masks on social life, behavior, and oral hygiene status and habits of everyday people are still unknown. The knowledge of the changes in patients' esthetic complaints, perceptions, and habits with the use of masks is essential for clinicians. Aim and Objectives The aim of the study was to evaluate the impact of the continuous use of face masks on oral hygiene habits; dental, smile and oral conditions, and self-perception; current reasons to seek dental care; and the importance attributed to teeth and smile esthetics among the adult population (students/employees) who wear masks 6 h per day for 6 months from August 30, 2021 to February 28, 2022. Materials and Methods An electronic survey (Google Forms) was used to generate a web-based platform for the responses in the form of a questionnaire. A link to the structured questionnaire was posted on Facebook, Instagram, Twitter, and WhatsApp. The study considered all the individuals willing to participate, and the subjects were informed about the survey's objectives. Data Analysis Method The recorded data were analyzed using the SPSS software. Proportions were compared using the Chi-square test. P < 0.05 was selected to denote statistical significance with the confidence level, and the significance level was set at 95% and 5%, respectively. Conclusion The study gave the current status of participants and their motivational levels toward seeking dental treatment, suggesting further studies in planning preventive strategies for the participants.